Study of the Active Components and Molecular Mechanism of Tripterygium wilfordii in the Treatment of Diabetic Nephropathy - Wang, Lin; Wang, Zheyi; Yang, Zhihua; Yang, Kang; Yang, Hongtao (Frontiers in Molecular Biosciences, 2021)
Explore the active ingredients and molecular mechanism of Tripterygium wilfordii (TW) in the treatment of diabetic nephropathy (DN) through network pharmacology and molecular biology. Firstly, Obtain the active ingredients and potential targets of TW through the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), use Cytoscape 3.7.2 software to construct the active ingredient-target network diagram of TW;Secondly obtain the target set of DN through the disease database, and Screen out the targets related to TW through the Venny diagram; construct a protein interaction network diagram (PPI) with the help of the String platform and Cytoscape 3.7.2; Third use the ClueGO plug-in tool to enrich the GO biological process and the KEGG metabolic pathway; Finally, it was verified by molecular docking experiments and cell pathways. As a result a total of 51 active ingredients of TW were screened, 126 predicted targets, and 44 target genes related to DN. The biological process of GO is mainly through the positive regulation of nucleotide metabolism, reactive oxygen metabolism, adipocyte differentiation, vascular endothelial cell migration, and cell response to vascular endothelial growth factor stimulation. KEGG enrichment analysis shows that the main pathways involved are insulin resistance, vascular endothelial growth factor, AGE-RAGE, NF-κB, HIF-1, TNF, IL-17, relaxin and other signaling pathways. It can be concluded from the data that TW may treat DN by regulating inflammatory immunity, cell apoptosis, oxidative stress, hemodynamics, insulin resistance, etc. It has the characteristics of multiple components, multiple targets, and multiple systems.